Pre-existing subclinical hypothyroidism and low free thyroxine in patients undergoing immune checkpoint inhibitor therapies is a risk factor for overt hypothyroidism - Bai, Yu; Yin, Yue; Liu, Hong (Frontiers in Endocrinology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have transformed cancer therapy. However, these therapies commonly precipitate immune-related adverse events, with thyroid dysfunction being the most frequent manifestation of endocrine toxicity. Whether subclinical abnormal baseline thyroid function (sABTF) predisposes to overt thyroid dysfunction during ICI therapy—and if so, how it influences time-to-onset, phenotype, severity, and clinical decision have not been fully elucidated.MethodsWe conducted a retrospective cohort study of 235 patients with cancer who underwent ICI therapy at Peking University Cancer Hospital between January 1, 2018, and September 30, 2024. Patients were stratified by baseline thyroid function status and monitored for ICI-induced overt thyroid dysfunction. Multivariate logistic regression analysis identified the risk factors for overt thyroid dysfunction. To examine baseline free thyroxine (FT4) cutoff, we used restricted cubic splines and receiver operating characteristic (ROC) analysis. Time-to-event was estimated using Kaplan-Meier curves and multivariate Cox models.ResultsAmong 99 patients with sABTF, 51.52% developed overt thyroid dysfunction during ICI therapy. Baseline FT4 was associated with overt hypothyroidism (adjusted odds ratio [OR], 0.88; 95% confidence interval [CI], 0.78–0.99; p = 0.037). A data-driven FT4 threshold of 13.91 pmol/L showed moderate discrimination (area under the ROC curve, 0.687). Using this threshold, higher FT4 (≥13.91 pmol/L) was associated with substantially lower odds of overt hypothyroidism (adjusted OR, 0.17; 95% CI, 0.06–0.47; p = 0.001), indicating that patients with FT4 <13.91 pmol/L were at markedly elevated risk. Severe subclinical hypothyroidism at baseline (TSH ≥10 mIU/L) was associated with a shorter time to overt hypothyroidism (median 7.78 weeks; adjusted hazard ratio [HR], 2.84; 95% CI, 1.42–5.67; p = 0.003), with the highest risk observed among patients who also had FT4 <13.91 pmol/L (median 6.57 weeks; adjusted HR, 10.05; 95% CI, 3.13–32.23; p < 0.001).ConclusionsPre-existing thyroid abnormalities, particularly severe subclinical hypothyroidism with concurrent FT4 <13.91 pmol/L, identify a high-risk subgroup prone to an earlier onset of ICI-induced overt hypothyroidism. These data support comprehensive baseline assessments and intensified early monitoring to enable timely detection and management during ICI therapy.